Manga! Manga! : - Schodt, Frederik L. (Kodansha International, 1983)
Manga can be fantastical and funny, or gritty and violent, with heroes as diverse as samural, sushi chefs, mah jongg masters, teenagers in love, and bored office workers, to say nothing of anthropomorphic cats and warrior robots.